The Works of John Dryden, Volume VIII : Plays: The Wild Gallant, The Rival Ladies, The Indian Queen - Dryden, John, 1631-1700 (Book collections on Project MUSE., 2013)
Volume VIII contains three of Dryden's Plays, along with accompanying scholarly appartus: Wild Gallant, Rival Ladies, and Indian Queen.